Complete genome sequence of sunflower ring blotch virus, a new potyvirus infecting sunflower in Argentina - Cabrera Mederos, Dariel; Bejerman, Nicolás; Trucco, Verónica; de Breuil, Soledad; Lenardon, Sergio; Giolitti, Fabián (Archives of virology, 2017)
The complete genome sequence of sunflower ring blotch virus (SuRBV), a previously undescribed potyvirus infecting sunflower in Argentina, is reported. The SuRBV genome comprises 9555 nucleotides (nt) and encodes a polyprotein of 3061 amino acids, flanked by 5′ and 3′ untranslated regions of 117 and 255 nt, respectively. Phylogenetic analysis showed that SuRBV belongs to the potato virus Y (PVY) subgroup and clusters together with sunflower chlorotic mottle virus and bidens mosaic virus. Percentage nucleotide identity between the whole genomes of SuRBV and BiMV was 70.6%, suggesting SuRBV should be considered a distinct species in the genus Potyvirus .